2021
DOI: 10.1016/j.celrep.2021.110099
|View full text |Cite
|
Sign up to set email alerts
|

Parity-induced changes to mammary epithelial cells control NKT cell expansion and mammary oncogenesis

Abstract: Pregnancy reprograms mammary epithelial cells (MECs) to control their responses to pregnancy hormone re-exposure and carcinoma progression. However, the influence of pregnancy on the mammary microenvironment is less clear. Here, we used single-cell RNA sequencing to profile the composition of epithelial and non-epithelial cells in mammary tissue from nulliparous and parous female mice. Our analysis indicates an expansion of gd natural killer T-like immune cells (NKTs) following pregnancy and upregulation of im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…There was evidence depicting that high BMI was associated with hay fever or other allergy diseases 35,36 . In previous studies, females with a history of pregnancy were identified to have decreased risk of endometrial cancer due to a fecundity effect, and the number of pregnancies is a proxy for a woman's ability to become pregnant, and thereby a healthy endometrium and endocrine system 37 . In our study, females with pregnancy history had higher risk of allergy, hay fever, and dog‐specific IgE, this might due to that the maternal immune system underwent major adaptive modifications during pregnancy and pregnancy history might change the immune microenvironment of women, 38,39 and thus the association between endometriosis and allergy, hay fever, and dog‐specific IgE was significant.…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence depicting that high BMI was associated with hay fever or other allergy diseases 35,36 . In previous studies, females with a history of pregnancy were identified to have decreased risk of endometrial cancer due to a fecundity effect, and the number of pregnancies is a proxy for a woman's ability to become pregnant, and thereby a healthy endometrium and endocrine system 37 . In our study, females with pregnancy history had higher risk of allergy, hay fever, and dog‐specific IgE, this might due to that the maternal immune system underwent major adaptive modifications during pregnancy and pregnancy history might change the immune microenvironment of women, 38,39 and thus the association between endometriosis and allergy, hay fever, and dog‐specific IgE was significant.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal models of mammary tumorigenesis and pregnancy have confirmed the protective effects of pregnancy in BC (Feigman et al, 2020;Hanasoge Somasundara et al, 2021). Interestingly, prolonged lactation and nursing have also been identified as key risk factors for inflammatory breast cancer (IBC), a rare and highly aggressive BC subtype (Mejri et al, 2020).…”
Section: Loss Of Irf5 Expression Alters Normal Mammary Gland Developm...mentioning
confidence: 99%
“…24,59 Given that pregnancy is one of the most important life history factors that modulates BC, such studies may allow for the identification of mechanisms and pathways that support the development of strategies for BC prevention. [60][61][62] Moreover, similar organoid systems could support the study and characterization of BC tissue obtained from pregnant women, thus enabling the investigation of cancer-associated mechanisms ex vivo that were present during in vivo development.…”
Section: Normal and Neoplastic Breast Systemsmentioning
confidence: 99%